THE URGENCY OF QANUN TO IMPLEMENT BIREUEN AS A SANTRI CITY - Eriani, Dian (Fakultas Hukum, Universitas Samudra, 2024)
Bireuen Regent's Decree Number 553 of 2020 designated Bireuen as a Santri City. As a Santri City, the behavior and conduct of the community is expected to reflect the objectives of this establishment, namely as a center for Islamic education, a model of Dayah education, and an Islamic reference center in Aceh. Apart from that, the aim of this determination is to make the people of Bireuen individuals who have good morals, are religious, and love science, as well as to ensure that the Bireuen region, especially Aceh in general, becomes a just and prosperous area. Apart from that, a road map for Bireuen as a Santri City in Aceh needs to be drawn up. Until now, Bireuen district does not yet have a Regional Regulation that regulates the implementation of Bireuen as a Santri City. Therefore, the urgency of qanun regarding the implementation of Bireuen as a Santri City in Bireuen district is a problem in this research. This research uses empirical legal research methods with a qualitative approach. Even though the government has issued a policy through Decree of the Regent of Bireuen Number 774 of 2021 concerning the Determination of the Study of Baksul Masail Khasanah Bireuen Santri City and Circular Letter Number 451/975/2020 concerning the Implementation of Bireuen as a Santri City, the implementation has not gone as expected. The implementation of Bireuen as a Santri City will not be optimal if only a few aspects of community life are regulated. Therefore, to achieve this goal, regulations are needed that regulate every aspect of the diverse social life of the community, so that they can become a supporting pillar in the implementation policy of Bireuen as a Santri City. With the existence of Qanun, technical and administrative needs related to this matter can be implemented optimally.